Long-Term In Vitro Passaging Had a Negligible Effect on Extracellular Vesicles Released by Leishmania amazonensis and Induced Protective Immune Response in BALB/c Mice. (24th December 2021) - Dupin, Talita Vieira; Reis, Natasha Ferraz de Campos; Perez, Elizabeth Cristina; Soares, Rodrigo Pedro; Torrecilhas, Ana Claudia; Xander, Patricia
Abstract : Depending on Leishmania species and the presence/absence of virulence factors, Leishmania extracellular vesicles (EVs) can differently stimulate host immune cells. This work is aimed at characterizing and evaluating the protective role of EVs released by Leishmania amazonensis promastigotes under different maintenance conditions. Initially, using a control strain, we standardized 26°C as the best release temperature to obtain EVs with a potential protective role in the experimental leishmaniasis model. Then, long-term (LT-P) promastigotes of L. amazonensis were obtained after long-term in vitro culture (100 in vitro passages). In vivo -derived (IVD-P) promastigotes of L. amazonensis were selected after 3 consecutive experimental infections in BALB/c mice. Those strains developed similar lesion sizes except for IVD-P at 8 weeks post infection. No differences in EV production were detected in both strains. However, the presence of LPG between LT-P and IVD-P EVs was different. Groups of mice immunized with EVs emulsified in the adjuvant and challenged with IVD-P parasites showed decreased lesion size and parasitic load compared with the nonimmunized groups. The immunization regimen with two doses showed high IFN- γ and IgG2a titers in challenged mice with either IVD-P or LT-P EVs. IL-4 and IL-10 were detected in immunized mice, suggesting a mixed Th1/Th2 profile. EVs released by either IVD-P or LT-P induced a partial protective effect in an immunization model. Thus, our results uncover a potential protective role of EVs from L. amazonensis for cutaneous leishmaniasis. Moreover, long-term maintenance under in vitro conditions did not seem to affect EV release and their immunization properties in mice.